The Role of Islamic Religious Education Teachers in Forming Students' Religious Character Through Learning Ability and Morality - Umma Rohmah Sholekah; Meti Fatimah (Abjadia : International Journal of Education, 2026)
This study aims to describe the role of Islamic Religious Education (Pendidikan Agama Islam/PAI) teachers in shaping students’ religious character through Aqidah Akhlak instruction at MI Sultan Fatah Demak, Central Java, Indonesia. Using a descriptive qualitative approach, the study involved 12 participants, including PAI teachers, the madrasah principal, and students. Data were collected through observations, interviews, and documentation, and analysed thematically. The findings show that PAI teachers play a strategic role as educators, spiritual guides, and moral role models in fostering students’ religious discipline, moral awareness, social ethics, religious understanding, and self-control in responding to negative influences, including digital media. The internalisation of Islamic values is strengthened through the integration of cognitive, affective, and behavioural aspects in learning, supported by religious habituation practices and collaboration between the madrasah and families. However, this study is limited to a single madrasah in a specific geographic context, which may restrict the generalisability of the findings.